Harmonic Analysis of 3-Phase Induction Motor at PT. Indocement Tunggal Prakarsa - Rahmat Adiprasetya Al Hasibi; Slamet Suripto; Rama Okta Wiyagi; Candra Dwi Sukardi; Yessi Jusman; Teguh Iman Prasetyo (Universitas Muhammadiyah Yogyakarta, 2019)
In a developing country, the rate of electricity demand is increasing along with the increasing rate of population growth and the rate of economic development of the country. With the growing development of the use of electronic technology in power systems, more and more non-linear equipment is used in the industry. This non-linear equipment can affect power quality because this non-linear load is the primary source of harmonic interference. To minimize the impact of the harmonic generation that occurs on non-linear loads such as induction motors, harmonic filter equipment is needed. This study also compared the current and voltage THD levels based on the IEEE standard and performed calculations to design a single tuned passive filter. This calculation is done because of the emergence of harmonics on a 3-phase induction motor that has exceeded the standard limit, so it must reduce the harmonics. Moreover, disturbances that occur, such as torsion vibrations caused by the interaction of the fundamental harmonic magnetic field, causing higher noise. Furthermore, it leads to additional thermal stress on electric motors, which have an impact on reducing the life of motor insulation. Based on the comparison and analysis obtained that the measured current THD still exceeds the IEEE standard limits. Then the interference that arises in the 3-phase RAW MILL induction motor will have an adverse impact if not handled correctly and adequately.